Development of a high clearance android-controlled inter-row weeder for rice intensification system - Suleiman, Samaila (2017)
Research was carried out to develop a high clearance inter-row weeder machine with Android control system, to address the challenge of high crop damage associated existing inter-row weeding machines due to low ground clearance under the system of rice intensification. This research was carried out in three main stages namely: Preliminary studies to evaluation of some existing inter-row weeders, Development of a prototype high clearance Android controlled weeding machine and Evaluation of the prototype machine.